E-COMMERCE APPLICATIONS ON FACEBOOK IN TURKEY: TESBİHANE AND ÇAYKUR - Erol Sercan YARALI (Fırat University, 2019)
The advancement in communication technologies has led to the progress of new terms and fields. Having improved day by day, internet, social media and commercial terms studied in this article has been gathered and assessed under a single roof. The transformation of internet technology has led the emergence of e-trade and made the marketing and delivery of goods to customers cheaper and easier without time and location limitations. Small and medium sized enterprises have attained a little share in these tough competitive conditions; so the employment share obtained in e-trade and the opportunity of supplying wide-range of goods with little budgets have been encouraging the companies to venture into e-trade. Firms operating in e-trade have to reach to the customers directly right away. In line with the advancement of social media they have offered various choices in respect to customers’ interests and run commercial campaigns. The advancement of internet technology accelerates the interactions, so customer or consumer becomes more active. This situation makes producers focus on consumers and analyze their needs. The people marketing on internet depict a portrait of conscious and cultivated consumers visiting another web-site when their demand is not met. That is why firms should manage their social media policy very well. Social media networks enforce the firms to collaborate with each other. As a result of business partnerships, the firms are able to supply products to the customers and have planned to reach mass people with a limited budget. In this study how social media has affected the commercial performance and e-trade strategies of Caykur and Tesbihane venturing into e-trade nowadays have been investigated, carrying out comprehensive interviews.